Respons Pertumbuhan dan Hasil Kacang Hijau Lokal Malaka Terhadap Kombinasi Doses Pupuk NPK dan Jenis Pupuk Hayati di Lahan Kering Nusa Tenggara Timur - Maria Klara Salli; Masria Masria; Yosefina Lewar (Politeknik Negeri Lampung., 2026)
Mung bean is a legume high in plant protein. Malaka mung beans have about 15% protein and up to 60% antioxidants. However, their productivity is lower than that of superior varieties. This study analyzed how different NPK doses and biofertilizer types affect the growth and yield of local Malaka mung beans, and identified the best combination. This experiment used a factorial Randomized Block Design with two factors: NPK dose (100 kg ha⁻¹ (N1) and 50 kg ha⁻¹ (N2) and biofertilizer type (no biofertilizer (P0) Bioboost (P1) Bion Up (P2), and Extragen (P3). Data were analyzed by ANOVA and Duncan’s Multiple Range Test. Soil samples were compositely analyzed to assess changes in pH, organic carbon, cation exchange capacity (CEC), and base saturation before and after the study. The results showed an interaction between treatments on stem diameter and seed yield per plot. The largest stem diameter and seed yield were obtained with 50 kg ha⁻¹ NPK + Extragen biofertilizer. The highest seed yield per plot was 153.78 g, equivalent to 1.28 t ha⁻¹. This yield was 40% higher than farmers’ yields, but reached only 64% of the yield of nationally superior mung bean varieties. These findings provide a vital foundation for developing a cultivation technology package for local mung beans in the drylands of East Nusa Tenggara. By advancing environmentally friendly agricultural inputs and strengthening food security rooted in local commodities, this work will make a significant contribution to sustainable development in the region.